(untitled) (Journal of Comparative Social Work, 2013)
In this essay, a critical incident involving an experienced child protection social worker and a First Nation family is deconstructed utilizing Jan Fook’s Critical Reflection Technique (2002). This deconstruction process investigates the issues of professional boundaries, revictimization, vicarious trauma, power and oppression and the ideas surrounding what a “real” and “good” social worker is. Through the reconstruction process, it is discovered that the assumptions underlying these issues are not helpful, and in fact are harmful to both the social worker’s sense of self as well as to social work practice. A discussion on how to avoid succumbing to the assumptions and expectations is then generated as a means to encourage professional practice without fear. Lastly, a strength-based perspective will be utilized to demonstrate how theory was operationalized with this First Nation family.